Model Pembelajaran E-Learning dalam Meningkatkan Keterampilan Menulis Teks Eksplanasi - Ai Sri Wahyuni; Iis Ristiani (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
Someone who cannot attend conventional education due to various causative factors, such as having to work (time constraints), geographical conditions (geographical constraints), long distances (distance constraints), physical conditions that are not possible (physical constraints), the capacity of conventional schools that are not possible (limited available seats), phobia of school, dropping out of school, or because they are educated through family education at home (home schoolers) it is possible to be able to keep learning, namely through e-Learning. E-learning or distance learning is expected to improve the quality of learning. This study used an experimental method by providing treatment. The class was divided into two groups, namely the experimental class with the e-learning model and the control class with conventional learning methods. In this study, researchers used a quantitative approach method. The result of this study is to find out the difference between learning with e-learning models with conventional learning.